Semi-collusion in media markets - Ralf Dewenter; Justus Haucap; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
This paper explores the effects that collusion can have in newspaper markets where firms compete for advertising as well as for readership. We compare three modes of competition: i) competition in the advertising and the reader market, ii) semi-collusion over advertising (with competition in the reader market), and iii) (full) collusion in both the advertising and the reader market. We find that semi-collusion leads to less advertising (but higher advertising prices) and lower copy prices which is beneficial for readers. Under certain circumstances, semi-collusion may even benefit advertisers as newspaper circulation is higher. In addition, total welfare may rise due to semi-collusion. Results under full collusion are ambiguous. However, even under full collusion newspaper copy prices may decrease and welfare may increase.
Keywords: L40; L82; D43; K21; 330; Media Markets; Collusion; Two-Sided Markets; Zeitung; Wettbewerbsbeschränkung; Medienökonomik; Wohlfahrtseffekt; Theorie